DILEMA DUALISME HUKUM KASUS MERARIQ KODEQ SUKU SASAK - Yayuk Kusumawati (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
The government had set several roles to manage social-life. One of these roles is about marriage accordance to Article/ section 1 of Constitution year 1974. Refer to it, someone who wants to marry has to be maturity of soul or physical, it meant that they will get harmony life at household. However, the fact describes that the roles cannot be practiced finely and face some obstacles such as the support roles, social - condition, economic, culture and religion. The effect of these situation, there are some problem formulations; (i) how much frequency of marry earlier or merariq kodeq at Sasak community. (ii) what of the cause merariq kode is still done even though they are in modern community. Meanwhile, the research has purposes to know (iii) the effects of marry earlier or merariq kodeq at Sasak Community, (iv) what the effort of government to prevent marry earlier or merariq kodeq at Sasak Community. The style of this research is Normative – sociological which is to know the circumstances in community. The method of data collecting is observation, interview, and documentation. Meanwhile, to analyze the data, researcher use qualitative description method. The result of research show that the obstacles to use the roles cause by lack of punishment and difficult access. The performance of early marry or merariq kodeq is to be culture at Sasak Community, it cause by custom roles demand although the bill number 1 year 1974 prohibit it. So, it be great obstacle to realize the role.